Respostas
respondido por:
2
Oi
Primeiramente resolva o que está dentro dos parênteses( )
(3+9)* (3 - 9)
12*- 6 * ( significa multiplicação)
3+9=12
3-9=-6
Agora multiplica
12*-6=
¹
12
-6x
- 72
Tenha excelentes estudos!!!
Primeiramente resolva o que está dentro dos parênteses( )
(3+9)* (3 - 9)
12*- 6 * ( significa multiplicação)
3+9=12
3-9=-6
Agora multiplica
12*-6=
¹
12
-6x
- 72
Tenha excelentes estudos!!!
respondido por:
2
3+9 12 3--9 6
espero ter ajudado
espero ter ajudado
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás